Research on improving urban park green space landscape quality based on public psychological perception: a comprehensive AHP-TOPSIS-POE evaluation of typical parks in Jinan City - Cheng, Qingtao (Frontiers in Psychology, 2025)
During rapid urbanization, environmental issues significantly affect urban residents health. Urban parks and green spaces play a crucial role in urban planning and layout, significantly impacting residents quality of life and livability. This study constructs a comprehensive landscape evaluation model, “AHP-TOPSIS-POE” from the perspective of behavioral psychological perception. It uses four urban parks in Jinan City (Qianfoshan Park, Baotu Spring Park, Daming Lake Park, and Quancheng Park) as case study samples. This method validates its feasibility by converting subjective perceptions into objective data. The research findings are as follows: (1) Urban park green space landscapes are significantly correlated with public psychological recovery; (2) The weight ranking of the criteria layer is as follows: Landscape Perception (B4) 0.5135 > Social Interaction (B3) 0.3015 > Spatial Form (B2) 0.1244 > Visual Quality (B1) 0.0606; (3) The relative closeness ranking of the four typical urban parks in Jinan City is as follows: Qianfoshan Park > Quancheng Park > Daming Lake Park > Baotu Spring Park. This study aims to reduce the subjectivity of evaluation indicators, raise public awareness of high-quality cognition and emotional experiences, and provide a scientific basis for the development of scientifically reasonable urban park green landscapes.